Novel Homozygous Mutation in the AGPAT2 Gene in a Child With Berardinelli-Seip Congenital Lipodystrophy Syndrome - Ahya Zaridoust; Ali Rabbani; Sima Hosseinverdi; Pascale Hilbert; Nima Rezaei (Acta Medica Iranica, 2018)
Berardinelli-Seip congenital lipodystrophy (BSCL) is an autosomal recessive disorder, characterized by the generalized absence of subcutaneous fat and muscular hypertrophy. Meanwhile other signs and symptoms have already been reported with this genetic disorder. Herein, we report an infant with BSCL, who was referred to our center because of acromegaloid and muscular appearance from the age of three months. He had dark skin, hypertrichosis prominent subcutaneous vessels and organomegaly in physical examination. Genetic study showed novel homozygous mutations in the AGPAT2 gene, which confirmed diagnosis of BSCL in this patient. Although clinical suspicious could help us to make diagnosis of congenital disorders, definite diagnosis relies on genetic studies.